Knowledge mapping of paediatric fever-a visual analysis based on CiteSpace - Di Liu; Di Liu; Dingruo Zhang; Tianyuan Yu; Sheng Guo; Xiaona Xue; Hui Hu; Jiayue Liu; Yue Xu; Narentuya (Frontiers Media S.A., 2024)
ObjectiveThis study aimed to analyse the research hotspots and frontiers in the field of paediatric fever between 2013 and 2023.MethodsThe included articles were visually analysed using CiteSpace 6.1.R6 software.ResultsA total of 2,662 Chinese-language articles and 1,456 English-language articles were included in the study. Based on the Chinese literature, research groups were identified represented by Xinmin Li, Jinling Hong and Hongshuang Luo. Based on the English literature, research groups were formed represented by Henriette Moll, Santiago Mintegi and Elizabeth Alpern. Tianjin University of Traditional Chinese Medicine was the institution with the largest number of publications in the Chinese literature, and the Centers For Disease Control And Prevention was the institution with the largest number of publications in the English literature. The research on paediatric fever mainly focused on mechanism exploration, green treatment and clinical management.ConclusionSeveral relatively stable research groups have been formed. Future studies on the differential diagnosis, rational drug use, standardised management and clinical practice guidelines for paediatric fever are needed.